Function Analysis of the ERF and DREB Subfamilies in Tomato Fruit Development and Ripening - Zhang, Li; Chen, LiJing; Pang, ShengQun; Zheng, Qun; Quan, ShaoWen; Liu, YuFeng; Xu, Tao; Liu, YuDong; Qi, MingFang (Frontiers in Plant Science, 2022)
APETALA2/ethylene responsive factors (AP2/ERF) are unique regulators in the plant kingdom and are involved in the whole life activity processes such as development, ripening, and biotic and abiotic stresses. In tomato (Solanum lycopersicum), there are 140 AP2/ERF genes; however, their functionality remains poorly understood. In this work, the 14th and 19th amino acid differences in the AP2 domain were used to distinguish DREB and ERF subfamily members. Even when the AP2 domain of 68 ERF proteins from 20 plant species and motifs in tomato DREB and ERF proteins were compared, the binding ability of DREB and ERF proteins with DRE/CRT and/or GCC boxes remained unknown. During fruit development and ripening, the expressions of 13 DREB and 19 ERF subfamily genes showed some regular changes, and the promoters of most genes had ARF, DRE/CRT, and/or GCC boxes. This suggests that these genes directly or indirectly respond to IAA and/or ethylene (ET) signals during fruit development and ripening. Moreover, some of these may feedback regulate IAA or ET biosynthesis. In addition, 16 EAR motif-containing ERF genes in tomato were expressed in many organs and their total transcripts per million (TPM) values exceeded those of other ERF genes in most organs. To determine whether the EAR motif in EAR motif-containing ERF proteins has repression function, their EAR motifs were retained or deleted in a yeast one-hybrid (YIH) assay. The results indicate that most of EAR motif-containing ERF proteins lost repression activity after deleting the EAR motif. Moreover, some of these were expressed during ripening. Thus, these EAR motif-containing ERF proteins play vital roles in balancing the regulatory functions of other ERF proteins by completing the DRE/CRT and/or GCC box sites of target genes to ensure normal growth and development in tomato.